Atypical parkinsonian syndromes - Burn, David (Henry Stewart Talks, 2007)
Types of atypical parkinsonian syndromes, Descriptive epidemiology, Clinical features, Cognitive and neurobehavioural aspects, Pathology and aetiology, Natural history, Structural and functional investigations, Clinical management, Future research directions